Examination of radial force with finite element method in switched reluctance motor - Polat, Mehmet; Öksüztepe, Eyyüp; Omaç, Zeki; Yıldırım, Merve; Kürüm, Hasan (My University, 2013)
The aim of this study is computation of radial forces shown as one of the main and important reasons of noise in Switched Reluctance Motor (SRM). In this paper, radial forces in saturation and unsaturation regions of a standart submersible pump type 8/6-pole SRM have been calculated and their changes have been obtained. ANSYS 10.0 package program which makes a solution with Finite Element Method (FEM) has been used for computation of radial forces. After geometric shapes are given, radial forces have been calculated from unaligned position of rotor towards aligned position with angle of one degree according to different current values.
Bildiri - Yayımlanmamış
Keywords: Switched reluctance motor